Strategi Bisnis Startup Social Enterprise Wahyoo Dalam Menghadapi Situasi Pandemi Covid-19 - Siti Qonaah (Cakrawala - Jurnal Humaniora, 2021)
Wahyoo's entrepreneurial startup is a technology company established in 2017 and provides added value that is beneficial to stalls in Indonesia. Wahyoo experienced the Covid-19 Pandemic crisis so that Wahyoo's income decreased by 50%. Warung Tegal (warteg) is a Micro, Small and Medium Enterprise that is affected by a policy issued by the government to break the chain of covid distribution, namely regional quarantine, large-scale social restrictions (PSBB) and lockdown. For that we need digital technology such as social entrepreneur startup Wahyoo which in carrying out its business strategy can face the Covid-19 pandemic. The purpose of this research is to describe what Business Strategy steps carried out by Wahyoo's social enterprise startups in the face of the COVID-19 pandemic situation. In this study, researchers used a qualitative approach and case studies. With the observation and documentation research method as a research method that illustrates that the Wahyoo Social Enterprise Startup Business Strategy steps that have been implemented through # Rantang Hati, Warteg New normal and opening new units can deal with the COVID-19 Pandemic Situation